Correlation Between Skin Autofluorescence and Muscle Activities of Lower Limb in Aging Without Disease and Disability. (December 2022) - Kaneko, Kenichi; Makabe, Hitoshi
Skin autofluorescence is a useful index to estimate the accumulation of advanced glycation end-products in human tissues. Elderly persons with higher skin autofluorescence have lower muscle mass, muscle strength and muscle power, however, little is known about the relationship between the skin autofluorescence level and each muscle activity. We measured the values of skin autofluorescence from five places on a lower limb, and the signals of surface electromyogram during isometric contractions from five muscles on that, simultaneously. The waveforms of surface electromyogram were analyzed by Daubechies-4 wavelet transformation. The value of skin autofluorescence was increased in the proximal part of the lower limb compared with the value of the distal part. The principal component of surface electromyogram activity in a time-frequency domain was lower in the proximal part compared with that of the distal part. There was a weak negative correlation between the value of skin autofluorescence on the gluteal region and the value of the mean wavelet coefficient of the surface electromyogram signals within the gluteus maximus muscle. The higher accumulation of advanced glycation end-products on the gluteal region might suggest the lower muscle activity in aging without disease and disability.